Molecularly imprinted polymer for solid-phase extraction of ephedrine and analogs from human plasma - Lasáková, Martina; Thiébaut, Didier; Jandera, Pavel; Pichon, Valérie (Journal of separation science, 2009)
A molecularly imprinted polymer (MIP) was synthesized and evaluated to selectively extract ephedrine from human plasma. The MIP synthesis was performed in chloroform with methacrylic acid as a functional monomer and the target alkaloid as a template molecule. The resulting MIP was applied to the selective extraction of ephedrine from a pure aqueous medium. A recovery about 74% was obtained using the MIP with only 7% on the nonimprinted polymer (NIP). A very straightforward selective SPE procedure was then successfully applied to the direct extraction of ephedrine from spiked human plasma with a high extraction recovery (68%) on the MIP with no recovery on the NIP. Moreover, the MIP was used for the selective extraction of catecholamine neurotransmitters, i.e. adrenaline and noradrenaline.
Keywords: polymery; extrakce na pevné fázi; financování organizované; Ephedrine; vysokoúčinná kapalinová chromatografie; Molecular Structure; Solid Phase Extraction; Financing, Organized; Polymers; molekulární struktura; lidé; kalibrace; efedrin; Calibration; Chromatography, High Pressure Liquid; molekulový imprinting; Molecular Imprinting; Humans